Immersed with Grit: Probing the Mindset of Future Hospitality Professionals - et. al., Ashika Miriam Tharakan , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Studies in the past have aimed to identify several factors that would encourage academic success among students. In recent times, the focus has shifted to understanding the impact or the influence of non-conventional factors such as Grit and Flow on the performance of students. In the current study, We have identified the relationship between the Grit and the get into a state of flow. The sample for this study consisted of 301 college students pursuing their education in hotel management from colleges in and around Bengaluru City. The data was collected through a questionnaire which was circulated through e-mail and social media of students. The scale used to measure Grit was the 10-item Grit Scale by Angela Duckworth and the 14 Items scale by Kazuki Yoshida was used to measure Flow. Statistical methods such as correlation, regression, t-test and ANOVA were applied in this study. Findings of the study indicate that the grit of hospitality students plays a role in their ability to enter into a state of flow.It is more likely for grittier individuals to experience flow. The levels of grit do not vary in terms of Gender, but it does with respect to year of education. The Flow levels vary between men and women, but it does not differ with year of education.